An areal typology of clause-final negation markers in northern sub-Saharan Africa and their historical relation with phasal polarity expressions - (:unkn) unknown (My University, 2018)
Clause-final negation markers (CFNMs), although typologically rare, can be found in a very wide range of languages of northern sub-Saharan Africa (NSSA). Given that on the one hand, CFNMs tend to occupy the same constructional slot as phasal polarity expressions (PPEs), and on the other hand, strong semantic and often also formal links are known to exist between PPEs and negation, CFNMs may be expected to often develop out of PPEs. However, this expectation is not borne out by the data available on the development of CFNMs in the languages of NSSA.This paper has two objectives. First, based on a sample of 618 African languages, it provides an analysis of spatio-temporal language dynamics in sub-Saharan Africa with respect to the feature CFNM. I argue that it is important to consider together the languages that have the feature under investigation and the languages that do not have it. Furthermore, in order to better capture the diversity of the languages that have CFNMs, I increase the degree of granularity of my data by taking into account two parameters, viz. obligatoriness of CFNMs and possible restrictions on the freedom to use CFNMs in different constructions. The spatial analysis of the data suggests that we need to distinguish two focal areas of the feature CFNM. The first one, the Central Focal Area, is the most prominent of the two and spans the east of West Africa and parts of Central Africa. The second one, the Western Focal Area, is less prominent and is restricted to West Africa. The two focal areas are separated by a major discontinuity around Ghana, Togo and Benin.Second, I discuss a number of cases from Mande languages where CFNMs happen to be historically related to PPEs. In line with the general rarity of the change from a PPE to a CFNM, CFNMs originating in PPEs tend to remain restricted to certain TAM constructions and not to evolve into default CFNMs. In those rare cases where PPEs do evolve into default CFNMs, this evolution is no
Keywords: African Research